UNVEILING IDEOLOGICAL CONFLICT IN INTERCULTURAL MATRIMONY: EXPLORING CLASHING CONVICTIONS IN MARIO PUZO’S “THE GODFATHER” - Ardianto, Rizqi; Zuhrul Anam (English Literature Department, Faculty of Economics, Law, and Humanities, 2024)
This study explores the ideological conflict within intercultural marriages as portrayed in Mario Puzo’s renowned novel, “The Godfather”. Utilizing a qualitative approach and Althusser’s theory of Ideological State Apparatuses (ISAs), the researchers delve into Puzo’s intricately woven narrative, highlighting the inherent tension arising from the collision of different values, traditions, and beliefs. The main focus is on the discord experienced by characters from diverse cultural backgrounds. In line with the ideological framework, this study found that a dominant ideology often subjugates other beliefs. Through comprehensive analysis, the researchers discovered that these conflicting beliefs significantly shape the characters’ societal perspectives. This research provides valuable insights into intercultural marriages, emphasizing the universal challenges presented in the novel that stem from negotiating differing beliefs within family and society.